Finite element analysis on burst pressure of defective steel pipes - Norhaida, Ab. Razak; Nasrul Azuan, Alang; Khairidz Azuwar, Safie; Ahmad Syahrizan, Sulaiman (2012)
Pipelines are often subject to damages due to corrosion and third-party accidents such as gouges and dents. The effect of gouge depths on burst pressure of steel pipes was studied using a nonlinear finite element (FE) method combine with stress modified critical strain (SMCS) model. The procedure in determining the SMCS model parameters from smooth tensile bars is systematically discussed in this paper. The SMCS model was used to determine the burst pressure as a function of gouge depths of different pipe diameters. The burst pressure from FE was then compared with values calculated using design codes for pipelines containing defect. The FE results show the ratio of wall thickness to pipe diameter have significant influence on burst pressure.